1984
DOI: 10.1038/jcbfm.1984.11
|View full text |Cite
|
Sign up to set email alerts
|

Local Cerebral Blood Flow with Fentanyl-Induced Seizures

Abstract: Summary: Local cerebral blood flow (LCBF) was eval uated with the [14C]iodoantipyrine quantitative autoradio graphic technique in 29 brain structures in conscious con trol rats and during fentanyl-induced electroencephalo graphic (EEG) spike and/or seizure activity and in the postseizure EEG suppression phase. During spike ac tivity, LCBF increased in all structures; the increase reached statistical significance (p < 0.05) in the superior colliculus, sensorimotor cortex, and pineal body (+ 130%, + 187%, and + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…The data on 1-CBF presented here and by Maekawa et al (13), and the data on 1-CMRgl presented by Tommasino et al (14) and Young et al (15), are consistent with the electrophysiologic work of Henriksen et al (16) and Nicoll et al (17), which showed that local deposition of P-endorphin or leucine-or methionine-enkephalin produced excitatory activity in the hippocampus or limbic system seizures. These findings for narcotics are similar to those for lidocaine, a compound that produces limbic system epileptogenic activity at fairly low doses compared to those required for cortical propagation (18,19).…”
Section: Correlation Of I-cbf and Eeg At Seizure Doses Of Fentanylsupporting
confidence: 90%
See 1 more Smart Citation
“…The data on 1-CBF presented here and by Maekawa et al (13), and the data on 1-CMRgl presented by Tommasino et al (14) and Young et al (15), are consistent with the electrophysiologic work of Henriksen et al (16) and Nicoll et al (17), which showed that local deposition of P-endorphin or leucine-or methionine-enkephalin produced excitatory activity in the hippocampus or limbic system seizures. These findings for narcotics are similar to those for lidocaine, a compound that produces limbic system epileptogenic activity at fairly low doses compared to those required for cortical propagation (18,19).…”
Section: Correlation Of I-cbf and Eeg At Seizure Doses Of Fentanylsupporting
confidence: 90%
“…They found marked increases in 1-CBF compared to controls in animals with seizures, but the basic pattern, including the predilection for limbic system structures, is similar to our findings. The increases in 1 -CBF noted by Maekawa et al (13) were considerably greater than the changes noted by us. However, the measurements we made were after 20 min of fentanyl infusion, and some of our animals were not actively seizing at the moment the CBF was measured.…”
Section: Correlation Of I-cbf and Eeg At Seizure Doses Of Fentanylcontrasting
confidence: 59%
“…An important question is to what extent opioid induced CNS over‐excitation may explain this apparent discrepancy. It is well established that administration of (synthetic) opioids may result in epileptiform activity (Urca et al , 1977; Carlsson et al , 1982; Maekawa et al , 1984; Tommasino et al , 1984; Young et al , 1984; Keykhah et al , 1985; Kofke et al , 1993; Cox et al , 1997). Seizure activity may be a confounding factor in the assessment of spectral EEG parameters of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on fentanyl-induced convulsive activity in rats by Carlsson et al [ 19821 indicated that there was a mismatch between cerebral blood flow and cerebral oxygen utilization [Carlsson et al, 19821, in that there was no increase in the blood flow to match the increased oxygen de:mand of the brain during seizure activity. However, Maekawa et al [1984] demonstrated that there was an increase in the blood flow and a decrease in the cerebrovascular resistance in all the structures during high-dose fentanyl-induced seizure activity time and that the flows remained elevated even during postseizure EEG suppression phase. Although there is increased EEG spike activity in the high-dose fentanyl group in the preischemic period, it appears that this effect of high dose fentanyl does not reflect changes in the latency of the SSER before inducing ischemia.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to their use in the clinical setting, opioids have become useful anesthetic agents in a variety of experimental studies [Carlsson et al, 1982;Maekawa et al, 1984;and Tommasino et al, 19841. Although opioids have been implicated in the pathophysiology of cerebral ischemic damage [Furui et al, 19841, the role of fentanyl in potentiating an ischemic/ reperfusion injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%